Penerapan Teknologi Pembangkit Listrik Tenaga Surya Di Kampung Konservasi Glintung RW 23 Kelurahan Purwantoro Kecamatan Blimbing Kota Malang untuk Ketahanan Energi dan Konservasi Lingkungan (TEKAD : Teknik Mengabdi, 2025)
Solar Power Plants (PLTS) have several advantages, including being environmentally friendly because they do not produce greenhouse gas emissions, saving operational costs in the long term, and being an abundant and renewable energy source. PLTS is very suitable for areas that get a lot of sunlight, such as tropical countries including Indonesia. The implementation of alternatives to reduce dependence on fossil energy is carried out with the activity theme "Application of PLTS Technology". This alternative is implemented in the form of community service in RW-23 Purwantoro Village, Blimbing District, Malang City. This activity ran for 6 months, thus turning RW-23 into a green, beautiful, cool and environmentally friendly conservation area. The activity carried out is the Implementation of PLTS in the context of Energy Conservation and Utilization of Renewable Energy. RW-23 administrators and local residents are generally quite appreciative of the idea of ​​"PLTS" to reduce dependence on fossil energy, environmental conservation and energy security in the RW-23 environment, thereby providing a positive impact, namely a clean, comfortable and sustainable environment. It is necessary to think about a cheaper "PLTS" design so that this idea will attract the attention and interest of RW administrators and other residents to be able to implement it in their own home environment on the basis of their own financing.